OPTIMIZING TRANSACTION MANAGEMENT FOR ENHANCED CUSTOMER LOYALTY IN THE DIGITAL ERA - Dr. Owa. Fredrick CNA; Patricia Ngozi Nwabudike; Mrs Nnabugwu Obiageli Chinwe (American Journals, 2024)
This paper examined the multifaceted dimensions shaping customer loyalty in the digital era, emphasizing the pivotal role of efficient transaction management. Through a comprehensive literature review, factors influencing customer loyalty such as convenience, personalization, trust, and security are explored, highlighting the critical importance of seamless transaction experiences. The study elucidates strategies for optimizing transaction management, including investments in technology, personalization of customer interactions, seamless omnichannel integration, and a focus on security and compliance. Additionally, case studies from Nigeria, including e-commerce platforms like Konga and Jumia, as well as loyalty programs from telecommunications companies and banks, underscore the tangible impact of optimized transaction management on increasing customer retention and loyalty. The paper concludes with actionable recommendations for businesses to enhance transaction management, emphasizing the significance of employee training, data analytics utilization, omnichannel integration, security measures, and the development of customer loyalty programs. By prioritizing efficient transaction processes and leveraging data-driven insights, businesses can foster enduring relationships with customers and thrive in the competitive digital landscape.
Keywords: Transaction management, Customer loyalty, Digital era, Optimization